Clinical outcomes after topography-guided LASIK: comparing results based on a new topography analysis algorithm with those based on manifest refraction. Issue 6 (June 2020) - Lobanoff, Mark; Stonecipher, Karl; Tooma, Tom; Wexler, Stephen; Potvin, Richard
Abstract : The Phorcides Analytic Engine provided an objective methodology for Contoura surgery planning that resulted in higher levels of 20/15 CDVA and UDVA postoperatively than was achieved using the manifest refraction. Abstract : Purpose: To compare short-term refractive and visual acuity outcomes after topography-guided laser in situ keratomileusis (LASIK) planned with a new topography analysis system to those based on the manifest refraction. Setting: Four clinical sites in the United States. Design: Double-arm, nonmasked, nonrandomized retrospective chart review. Methods: This was a retrospective study of postoperative refraction and visual acuity at least 2 months after uneventful LASIK using the Contoura Vision algorithm on the WaveLight Topolyzer VARIO laser. One arm comprised eyes treated using the manifest refraction (manifest), while the other included eyes treated with an ablation profile determined by the Phorcides Analytic Engine (analytic). Results: Clinical results from a matched group of 317 manifest eyes and 323 analytic eyes were available for analysis. Residual refractive results, both sphere and cylinder, were similar between groups. However, significantly more eyes had 20/16 or better (−0.1 logarithm of the minimum angle of resolution) uncorrected distance visual acuity (UDVA) (62.5% analytic, 41.3% manifest) and corrected distance visual acuity (CDVA) (77.1% analytic, 51.4% manifest) in the analytic group. All eyes but 1 had a CDVA of 20/20 or better postoperatively. The number of patients with a UDVA better than their preoperative CDVA was significantly higher in the analytic group (36.5%) relative to the manifest group (23.0%). No eye in either group lost more than 1 line of CDVA; significantly more eyes in the analytic group (42.7%) gained 1 or more lines of CDVA relative to the manifest group (30.3%). Conclusions: Using the Phorcides Analytic Engine for topography-guided surgery planning increased the likelihood of 20/16 UDVA and CDVA relative to using the manifest refraction.